The Effect of Profitability Collateralizable Assets and Growth in Net Assets to Dividend Policy (Case Studies on Manufacturing Companies Listed in Indonesia Stock Exchange for The 2018-2022 Period) - Ahmad Nurhadi; Bambang Widagdo; Erna Retna Rahadjeng; Hilda Sanjayawati (Universitas muhammadiyah malang, 2024)
This research aims to anlyze and obtain empirical evidence about the effect of profitability, collateralizable assets, and growth in net assets to dividend policy. Dependent variable was used Dividend Policy. Independet variable were used profitability, collateralizable assets, and growth in net assets. This research population was manufacturing companies listed in Indonesia Stock Exchange in period 2018-2022. Sample was collected by purposive sampling method. Total 35 manufacturing companies were taken as study’s sample. By collecting secondary data in the form of financial reports that are accessed through www.idx.co.id. Hypothesis testing used multiple linier regression analysis with SPSS 23 program and a significant level of 0,05 (5%). The results of this research showed that collateralizable assets did not significantly effect to dividend policy. As for profitability has positive significantly effect to dividend policy, and growth in net assets has negative significantly effect to dividend policy. The determination coefficient result showed 58,1%. That’s about 58,1% indicated the ability of the independent variables explained the dependent variable while 41,9% explained by the other variables.